ROLE OF EFFECTIVE COMMUNICATION IN ENHANCING DOG OWNER KNOWLEDGE ABOUT BREEDING PRACTICES IN PUNJAB - ROOPA, Y; KASRIJA, R; VERMA, H K; SINGH, P (The Indian Journal of Animal Reproduction, 2022)
At Teaching Veterinary University Hospital and various districts of Punjab, the dog owners (100 each from urban and rural area) were randomly selected and personally interviewed using pretested interview schedule. Breeding knowledge score of both groups was different (p<0.05), however, the knowledge level of both groups was under low category. A positive correlation (p<0.05) existed between breeding practice knowledge index and their communication profiles. The present study underlines the importance of communication profile in improving the knowledge level of dog owners about correct breeding practices.